Comparison of efficacy of paracetamol and ibuprofen for treatment of hemodynamically significant patent ductus arteriosus in preterm infants - R, Swathi; Shah, Maulik; Puthussery, Agnes (Indian Journal of Child Health, 2024)
Background: Indomethacin and ibuprofen (IBU) have been approved for the pharmacological closure of hemodynamically significant patent ductus arteriosus (hsPDA) in preterm infants. Recent works have demonstrated that paracetamol (PCM) can also be used but more research is required regarding efficacy and safety. Objectives: The objective is to compare the efficacy and safety of PCM and IBU for the treatment of hsPDA in preterm infants. Methodology: An observational study was designed with ethical clearance and parental consent. Patients were evaluated for hsPDA by clinical and 2 D echo findings. After inclusion and exclusion criteria, consecutive 100 patients were assigned between PCM and IBU and were given a 3-day course. After echocardiographic and clinical evaluation, if required, a second course with same drug was given. The outcome measures were the rate of ductal closure, the safety of drugs, and adverse events. Results: The PCM group had a closure rate of 76.25% and the IBU group had 75%. IBU had a significantly higher rate of closure in the first course (45% vs. 16.25%). The mean closure time observed was 4.54 days and 4 days for PCM and IBU, respectively. PCM gave a higher closure rate in the low-birth-weight group and where platelet counts were below normal. Regarding the safety aspect also no significant difference between groups was observed. Conclusion: PCM can be advised as a first-line treatment for hsPDA cases in preterm infants and is a better choice in cases of comorbidities and patients with low platelet count.